Childhood Psychological Distress and Healthy Cardiovascular Lifestyle 17–35 Years Later: The Potential Role of Mental Health in Primordial Prevention. Issue 8 (24th January 2018) - Winning, A; McCormick, M C; Glymour, M M; Gilsanz, P; Kubzansky, L D
Abstract : Individuals who experienced more psychological distress as children had less healthy lifestyles (considering smoking status, alcohol consumption, physical activity, diet, and body weight) as adults Abstract: Background: Maintaining a healthy lifestyle in adulthood has been shown to significantly reduce cardiovascular disease risk. Increasing evidence suggests that behavioral risk factors for cardiovascular disease are established in childhood; however, limited research has evaluated whether childhood psychological factors play a role. Purpose: To evaluate the association between childhood psychological distress and young to mid adulthood healthy lifestyle. Methods: Using prospective data from the 1958 British Birth Cohort, we assessed whether psychological distress in childhood (captured by internalizing and externalizing symptoms at ages 7, 11, and 16 years) predicted healthy lifestyle at ages 33 ( N = 10, 748) and 42 ( N = 9, 581) years. Healthy lifestyle was measured using an index previously demonstrated to predict cardiovascular disease, consisting of five components: absence of smoking, moderate alcohol consumption, regular physical activity, healthy diet, and ideal body weight. Results: Few participants (3.8% at age 33 years and 2.8% at age 42 years) endorsed all five healthy lifestyle components. Linear regression models, adjusting for potential child- and family-level confounders, revealed that higher distress levels in childhood were negatively associated with healthy lifestyle at age 33 years (β = −0.11, SE = 0.01, p < .001) and 42 years (β = −0.13, SE = 0.01, p < .001). Higher distress was also associated with significantly lower odds of endorsing each lifestyle component, except physical activity, at both ages. Additional analyses indicated that childhood distress levels were highest among those whose lifestyle scores were low at age 33 and further declined between ages 33 and 42. Conclusions: Psychological distress in childhood may indicate children at risk of less healthy lifestyle practices later in life. Although our findings are preliminary, psychological distress may also provide an important target for public health interventions aimed at preventing cardiovascular disease.